Covid-19 Prevention Behaviors and Social Support For Elderly Group in The Working Area of The Atambua City Puskesmas - A. Hati, Balbina; F.E Manurung, Imelda; O. Dodo, Dominirsep (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
The elderly group is a group at risk of exposure to COVID-19, so it is necessary to have COVID-19 prevention behaviors, such as knowledge, attitudes, actions and social support among the elderly group in the working area of the Atambua City Health Center, in Belu Regency. This research is a quantitative research using descriptive research methods. The number of samples in this study were 100 elderly people, in the work area of the Atambua City Health Center. With a random sampling technique, data collection used a questionnaire of knowledge, attitudes, actions, and social support which had been declared valid and reliable. The results of the study found that 86.0% of the elderly had good knowledge about preventing COVID-19, and 88.0% of the elderly who had a good attitude towards preventing COVID-19 were good at preventing COVID-19, as much as 83.0%. Meanwhile, the elderly who have good social support for preventing COVID-19 are 87.0%, in the working area of the Atambua City Health Center, Belu Regency. Keywords: Behavior, Social Support, Elderly, COVID-19.